Study on methanolic extracts of nauclea subdita (Korth) Steud : heartwood parts for the total phenolic contents and free radical scavenging activities - Fatin Ruzanna Jamaludin; Razak Wahab; Jamaluddin Mohd Daud; Mahmud Sudin; Mohd Sukhairi Mat Rasat; Othman Sulaiman (Maxwell Scientific Organization, 2012)
The present study investigated the Total Phenolic Content (TPC) and free radical scavenging activity of Nauclea subdita (Korth) Steud. which might reflect the potency of the plant extract as antioxidant. Young and matured trees of N. subdita were harvested and cut into three heartwood parts (top, middle and bottom) and grounded into powdered forms. Soxhlet extraction of the heartwood samples using polar (methanol) and non-polar (hexane) solvents and phytochemical screening tests were carried out. The total phenolic contents of the methanolic crude extracts from heartwood parts were determined by colorimetry at 760 nm using Folin-Ciocalteau’s reagent and gallic acid was used as standard. The methabolic extracts were also checked for primary antioxidant activities using an in vitro method, measured by free radical scavenging activity of 2, 2’-Diphenyl-1- Picrylhydrazyl (DPPH) radical. The absorbances were measured at 517 nm by UV/VIS spectrophotometer and compared with standards Trolox and Butylated Hydroxyanisole (BHA). The results from this study suggest that N. subdita heartwood extract may serve as a potential source of natural antioxidant for future development in food and nutraceutical applications.